Monetary policy deliberations: committee size and voting rules - Vincent Maurin; Jean-Pierre Vidal (European Central Bank (ECB), 2012)
How large should a monetary policy committee be? Which voting rule should a monetary policy committee adopt? This paper builds on Condorcet's jury threorem to analyse the relationships between committee size and voting rules in a model where policy discussions are subject to a time constraint. It suggests that in large committees majority voting is likely to enhance policy outcomes. Under unanimity (consensus) it is preferable to limit the size of the committee. Finally, supermajority voting rules are social contrivances that contribute to policy performance in a more uncertain environment, when initial policy proposals are less likely to be correct, or when payoffs are asymmetric.
Keywords: D71; D78; D81; E58; 330; Collective decision-making; deliberations; optimal committee sizing; voting rules